2019
DOI: 10.1016/j.pnpbp.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic terminals are the primary source of α2-adrenoceptor mediated dopamine release in the medial prefrontal cortex

Abstract: In various psychiatric disorders, deficits in dopaminergic activity in the prefrontal cortex (PFC) are implicated. Treatments involving selective augmentation of dopaminergic activity in the PFC primarily depend on the inhibition of α2-adrenoreceptors singly or in combination with the inhibition of the norepinephrine transporter (NET). We aimed to clarify the relative contribution of dopamine (DA) release from noradrenergic and dopaminergic terminals to DA output induced by blockade of α2-adrenoreceptors and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 63 publications
7
12
1
Order By: Relevance
“…Importantly, the loss of NET provides a likely explanation for why noradrenergic denervation failed to reduce extracellular DA in the mPFC (Harik, 1984;Carboni et al, 1990;Pozzi et al, 1994;Valentini et al, 2004;Masana et al, 2011;Devoto et al, 2015;Devoto et al, 2019), in apparent contradiction with our hypothesis that noradrenergic terminals supply extracellular DA in the mPFC. Indeed, in accord with this hypothesis, transient inactivation of noradrenergic neurons by clonidine perfusion into the LC, a condition in which NET activity is Dialysate levels are means ± SEM of values obtained in 9 control and 11 nisoxetine-perfused rats.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Importantly, the loss of NET provides a likely explanation for why noradrenergic denervation failed to reduce extracellular DA in the mPFC (Harik, 1984;Carboni et al, 1990;Pozzi et al, 1994;Valentini et al, 2004;Masana et al, 2011;Devoto et al, 2015;Devoto et al, 2019), in apparent contradiction with our hypothesis that noradrenergic terminals supply extracellular DA in the mPFC. Indeed, in accord with this hypothesis, transient inactivation of noradrenergic neurons by clonidine perfusion into the LC, a condition in which NET activity is Dialysate levels are means ± SEM of values obtained in 9 control and 11 nisoxetine-perfused rats.…”
Section: Discussioncontrasting
confidence: 97%
“…As Table 1 shows, consistent with earlier results (Devoto et al, 2015;Devoto et al, 2019), the ICV injection of aDBH (0.5 µg/5µl) depleted tissue and extracellular NE almost totally and did not modify tissue DA and DOPAC. Notably, in apparent contrast to our hypothesis that noradrenergic terminals supply DA in the mPFC, noradrenergic denervation did not reduce extracellular DA (actually increased it by about 38%) and reduced extracellular DOPAC by 50%.…”
Section: Raclopride Increases Extracellular Da In the Mpfc After Losssupporting
confidence: 91%
See 1 more Smart Citation
“…Generally, we found reduced DA levels in the striatum and prefrontal cortex of maternally separated (MS) rats when compared to nonseparated (NS) rats. These results were predictable as previous studies showed that chronic stress (including maternal separation) leads to central dopaminergic denervation in brain areas implicated in movement, learning and memory, or motivation [1,[92][93][94]. In an animal model of PD, 6-OHDA selectively uptaken by dopaminergic neurons via DA transporters can exacerbate the harmful effects of chronic stress leading to apoptotic cell death in the striatum and related brain areas including the prefrontal cortex and hippocampus [12,95,96].…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 81%
“…(4) Electrical stimulation of the LC did not change DA concentration in striatum but significantly increased NA level in this region (Devoto et al, 2005a,b). 5Selective lesion studies and specific disruption of catecholamine production in VTA and LC confirmed that noradrenergic terminals are the main source of dopamine in cortical regions (Pozzi et al, 1994;Devoto et al, 2008Devoto et al, , 2015Devoto et al, , 2019Smith and Greene, 2012). Moreover, several medications for neuropsychiatric conditions increase both DA and NA in the brain (Devoto et al, 2006).…”
Section: Da and Na Co-release From The Locus Coeruleusmentioning
confidence: 93%